2013
DOI: 10.2176/nmc.53.171
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hemodynamics After Placing Intracranial Stents

Abstract: Stent-assisted coil embolization has enabled the endovascular treatment of wide-necked cerebral aneurysms. Moreover, recent reports demonstrated that stent-assisted coil embolization was associated with a significant decrease in angiographic recurrences of coiled cerebral aneurysms. One of the possible explanations for this adjunctive effect of stent-assisted coil embolization is changes in the local hemodynamics caused by placing intracranial stents. This study investigated the hemodynamic effect of intracran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…14 RRT is an important parameter that reflects the disturbed blood flow and its prolonged residence time in the aneurysmal sac. Tanemura et al 6 demonstrated that a single Enterprise stent could increase the RRT by 20% in a previous CFD study. Our study further demonstrated that the RRT gradually increases by sequential stent placements, which would likely provide a better environment for thrombus formation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…14 RRT is an important parameter that reflects the disturbed blood flow and its prolonged residence time in the aneurysmal sac. Tanemura et al 6 demonstrated that a single Enterprise stent could increase the RRT by 20% in a previous CFD study. Our study further demonstrated that the RRT gradually increases by sequential stent placements, which would likely provide a better environment for thrombus formation.…”
Section: Discussionmentioning
confidence: 94%
“…5 Hemodynamic studies of saccular aneurysms have revealed that stent placement can reduce the impinge flow and wall shear stress (WSS); this effect may favor thrombus formation and consequently cure the aneurysm. 6 However, the morphology of fusiform aneurysms is entirely different from that of saccular aneurysms; this difference may result in unique flow patterns before and after stent placement. Most important, gaining knowledge of how intra-aneurysmal flow patterns change when the number of overlapping stents increases is of great importance because it may provide some evidence for optimizing stent-placement strategies.…”
Section: Abbreviationsmentioning
confidence: 99%
“…This STL file was imported into Magics (Materialise Japan), vessels less than 1 mm in diameter were eliminated, in principle, vessels in the region of interest were extracted, and, eventually, to correct the skewness of the triangle for the calibration of STL, the images were remeshed with triangles with a maximum length of 0.25 mm using 3-matic (Materialise Japan), and a patient-specific shape model was obtained after curvature smoothing. 10) …”
Section: Methodsmentioning
confidence: 99%
“…However, in researches on cerebral aneurysms using CFD analysis, the relationships of hemodynamic parameters with the occurrence, 6) enlargement, 7) and rupture point 8) of cerebral aneurysms and atherosclerotic lesions 9) have been evaluated, and hemodynamic changes due to stent placement 10) and prediction of the state of coil embolization 11) have also been reported. Recently, CFD analysis using morphologic data of ruptured cerebral aneurysms showed that the pathologically confirmed hemostatic pattern of ruptured cerebral aneurysm is related to stagnation and complex flow.…”
Section: Introductionmentioning
confidence: 99%
“…22,42 This is attributed to increase packing density and because the stent have a potential role in diverting flow away from the aneurysms. 43,44 Despite this, the long-term occlusion rate was in the 60-70% 22,42 with favorable clinical outcome and protection against future risk of aneurysm rupture. The use of a stent as an adjunct in aneurysm coiling requires the use of dual anti-platelets therapy (Fig.…”
Section: Aneurysm Sizementioning
confidence: 99%